AUDIT PROCEDURE: NEW PROCEDURE FOR REVIEWING SENTENCES IN UZBEKISTAN - Lawyer Z.S. Nazarov (Web of Journals Publishing, 2024)
In the science of criminal procedural law, the review of court decisions is perceived as a form of criminal procedural activity. It includes several types of review of court sentences and determinations, both those that have entered into legal force and those that have not. The functions of the appellate and cassation instances of the court consist precisely in the fact that at each of the specified stages, the legality of the sentence and determination of the court that considered the case in the previous instance is verified.
Keywords: review of court decisions, sentence, file an appeal, judicial errors, revision in the revision procedure, change of the sentence, complaints and protests in the revision procedure.